2010
DOI: 10.1111/j.1834-7819.2010.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of changing dental needs on cost savings from fluoridation

Abstract: Background: Although community water fluoridation has been one of the cornerstone strategies for the prevention and control of dental caries, questions are still raised regarding its cost-effectiveness. This study assessed the impact of changing dental needs on the cost savings from community water fluoridation in Australia. Methods: Net costs were estimated as Costs (programme) minus Costs (averted caries). Averted costs were estimated as the product of caries increment in non-fluoridated community, effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
(15 reference statements)
4
28
0
2
Order By: Relevance
“…These New Zealand and Australian studies detailed above are compatible with other studies which indicate cost savings from CWF in the US, [119,120] Australia, [121,122] and Quebec, Canada. [123] A modelling study on CWF in South Africa also reported that benefits of CWF would exceed costs.…”
Section: Health Inequalities and Cost Effectivenesssupporting
confidence: 77%
“…These New Zealand and Australian studies detailed above are compatible with other studies which indicate cost savings from CWF in the US, [119,120] Australia, [121,122] and Quebec, Canada. [123] A modelling study on CWF in South Africa also reported that benefits of CWF would exceed costs.…”
Section: Health Inequalities and Cost Effectivenesssupporting
confidence: 77%
“…9,30 Studies continue to find that community water fluoridation is cost saving. 21,[31][32][33] Trends in availability of fluoride sources. Community water fluoridation and fluoride toothpaste are the most common sources of non-dietary fluoride in the United States.…”
Section: Rationalementioning
confidence: 99%
“…88 Studies in the United States and Australia also have documented the cost-effectiveness of community water fluoridation. 21,[31][32][33] Safety of fluoride additives. Unique comments (about 300) expressed concern that fluoride is a poison and an industrial waste product; standard letters noted the lack of specific data on the safety of silicofluoride compounds used by many water systems for community water fluoridation.…”
mentioning
confidence: 99%
“…[18][19][20][21] In the absence of fluoridated water, caries experience of children has increased. An Australian dental health survey conducted in 2002 reported children residing in areas where the water contained negligible fluoride had poorer dental health than those residing in optimally fluoridated areas, regardless of socio-economic 122 ª 2011 Australian Dental Association…”
Section: Consumption Of Watermentioning
confidence: 99%